Pengaruh Penggunaan Metode Demonstrasi Terhadap Hasil Belajar PAI Kelas 8 Di SMPN 4 Lareh Sago Halaban - Mahyeldi Ansarulloh; Supriadi Supriadi; Alimir Alimir; Iswantir Iswantir (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This research is motivated by a phenomenon from the author's observations about the low student learning outcomes caused by several factors, including the low attention of students in attending Islamic Religious Education lessons. One of the causes of the problems that arise is the inaccuracy of the use of methods in learning. So, in this study the researcher will choose a method that is considered to be able to improve student learning outcomes, namely by using the demonstration method. This research uses a quantitative experimental approach. Collecting data in this study the authors obtained through tests and documentation. This study used 44 students as a population and 44 students as a sample. The data analysis technique that the author did was a prerequisite analysis test in the form of a data normality test, homogenesis. Then the final data analysis the author uses is the t-test. Based on the results of the study it can be understood that the results of the researchers' calculations using the t-test and SPSS 20 where the t-test obtained the results tcount = 4.11713736 and ttable = 1.714, then tcount > ttable then H0 is rejected and H1 is accepted, and calculations using SPSS 20 yield results which are 2-tailed significant values or sig values. (2-tailed) = 0.000 at the significance level α = 0.05. Because the significant value of 2-tailed <α, i.e. 0.000 <0.05, H0 is rejected. So it can be concluded that demonstrations are effective in improving student learning outcomes in class VIII.2 PAI subjects at SMPN 4 Kec. Lareh Sago Halaban.